COMPARATIVE EFFECTIVENESS OF SNAKEHEAD FISH AND BINAHONG EXTRACTS ON PERINEAL WOUND HEALING IN POSTPARTUM MOTHERS - Iswatun Khasanah; Anita Indra Afriani; Dewi Mayangsari (Universitas Karya Husada Semarang, 2026)
Background: Perineal rupture is a common childbirth injury that may delay recovery, increase the risk of infection, and reduce postpartum quality of life. Complementary therapies, including snakehead fish (Channa striata) extract and binahong leaf (Anredera cordifolia) extract, have shown potential to enhance wound healing through different biological mechanisms. However, comparative evidence regarding their effectiveness in postpartum perineal wound management remains limited.Objective: This study aimed to compare the effectiveness of snakehead fish extract and binahong leaf extract in accelerating perineal wound healing among postpartum mothers.Methods: A quasi-experimental study using a two-group pretest–posttest design without a control group was conducted among postpartum mothers with second-degree perineal rupture at Roja Asyifa Clinic, Pemalang Regency. Participants received either snakehead fish extract or binahong leaf extract for four consecutive days. Wound healing was assessed using the REEDA Scale before and after intervention. Data were analyzed using appropriate comparative statistical tests with a significance level of 0.05.Results: Both interventions significantly improved perineal wound healing (p < 0.05). The reduction in REEDA scores was greater in the snakehead fish extract group than in the binahong leaf extract group, indicating superior wound healing outcomes.Conclusion: Both interventions effectively accelerated perineal wound healing. Snakehead fish extract showed superior effectiveness and may serve as a promising complementary therapy for postpartum perineal wound management.